PREFERENSI KONSUMEN BUAH JERUK SIAM DI PASAR RAKYAT KRENENG KOTA DENPASAR - Alferia Yasinta Lembu; Ni Gst. Ag Gde Eka Martiningsih; I Ketut Arnawa; Yulianti Sapanca (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
This research is entiled “Consumer Preferences of Siamese Citrus Fruit in the Market the traditional of Kreneng Denpasar City. More and more Siamese oranges are entering local and modern markt because it is favored by consumrs, but the demamd the typs of Siamese orangs vary according to the type of orange that is used has its own charactructic. Consumer preferences for attributes and the type of orange that will determine how big the fruit is received and attractive to consumers. By formulating the problem whether the attributes that are become preferences and the most dominant attribute as consumer preferences in buying Siamese oranges at the Traditional Market Kreneng Denpasar City. With the aim of knowing the attributes of Siamese oranges to analyze the most dominant attribute as a preference in the Kreneng People’s Market Denpasar City. Research in conduted’ with 80 consumers, using judgment sampling technique the analytical method used in research on consumer preference on the attributes of Siamese oranges using a likert scale consisting of from a scor of one to five, while to determine the attributes of citrus fruit. Which is in accordance with consumers preference, multi-attribte analysis is fish block. The result of this study are that attributes that become consumers preference, namely; taste, price, color and size are that the most dominant consireded by consumers in buying Siamese oranges at Traditional Market Kreneng Denpasar City is the attribute of taste, with the highest of 16,7